Eclampsia: a Five-Years Analysis - Viviana Sáez Cantero (Medisur)
Background: eclampsia remains an important cause of maternal mortality and morbidity, mostly in developing countries. Objective: to determine the incidence and to characterize patients that were admitted with an eclampsia diagnosis in the "Enrique Cabrera" Teaching Hospital. Method: a descriptive and observational study was conducted in the "Enrique Cabrera" Teaching Hospital including all patients diagnosed with eclampsia who were admitted in the intensive care unit from January 2006 to December 2010. Data were obtained from medical records. Statistics SPSS 11,5 Windows system was used as well as frequency and percentage distributions for qualitative variables. Results: incidence of eclampsia was 9, 8 per 10000 births. 62, 1 % of patients were white skinned and 58, 6 % were adolescents. The average gestational age was 37, 6 ± 3, 3 and 89, 6 % of these patients required to be performed a cesarean (c-section). 55, 2 % of eclampsia cases appeared postpartum, most of them (81, 2 %) were early eclampsia. The constantly present symptom was headache (100 %) and 20, 7 % of patients presented complications. Conclusion: even when eclampsia incidence was not high in our setting, the prevalence of postpartum eclampsia forces us to reflect on the need to improve diagnosis and control of patients at risks.